(untitled) (Praxis Educativa, 2024)
The present article describes the main qualities and strategies of the school´s Principal leadership in a school in the region of Ñuble, Chile. The analysis of the case study is carried out by using a qualitative methodology with an interpretative approach, by means of the conduction and analysis of 12 interviews and 1 focus group to different actors of the educational community. Based on the methodology proposed by the International Successful School Principalship Project (ISSPP), we address the challenges posed in the context of school management, the contributions of the school management team, the integration of students coming from different social and cultural backgrounds, and the raising of achievement levels in the school. The study concludes that the qualities and strategies that characterize the school leadership evidence a successful leadership, as demonstrated by the integration of the three types of leadership: transformational, distributed, and pedagogical.